Apoptosis or senescence? Which exit route do epithelial cells and fibroblasts preferentially follow?. (June 2016) - Georgakopoulou, Eleni; Evangelou, Konstantinos; Havaki, Sofia; Townsend, Paul; Kanavaros, Panagiotis; Gorgoulis, Vassilis G.
Highlights: Epithelia continuously "change", while stroma remains "stable" with a potential regulatory role. Fibroblasts predominantly exert senescence when stressed. Epithelial cells preferentially respond via apoptosis under stress conditions. Novel therapies could aim in differential response between epithelium and stroma. Abstract: Senescence and apoptosis constitute types of cellular responses that normally ensure homeostasis, when endogenous or exogenous signals occur. Their deregulation is often observed in various pathologies, such as age and non-age related diseases including cancer. Although epithelial cells and fibroblasts are capable to exert both functions, under a plethora of insults, the fact that they exhibit notable intrinsic differences in cell/tissue homeostasis properties, might be a crucial determinant of the mode of response to a certain stress signal. Sparse evidence in the literature reveals that in the same tissue/organ context and under the same conditions, the cell type seems to drive the differential counteraction between epithelia and fibroblasts. Based on the above notion we propose that, upon stress insults, human fibroblasts seem to predominantly respond via senescence, while epithelial cells prefer to exert apoptosis. We suggest that considering the tissue as a whole (epithelium and stroma) would benefit research into new therapeutic strategies for chronic diseases and cancer.